2023
DOI: 10.3390/md21020102
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Bioaccessibility of Proteins and Bioactive Compounds of Wild and Cultivated Seaweeds from the Gulf of Saint Lawrence

Abstract: Despite the increased interest in macroalgae protein and fibers, little information is available on their bioaccessibility. The application of an in vitro gastrointestinal digestion model to study the degree of disintegration and release of proteins with expressed bioactivities from wild and cultivated Palmaria palmata and Saccharina latissima was proposed in this study. Macroalgae from the Gulf of St Lawrence, Canada, were submitted to digestive transit times of 2 (oral), 60 (gastric) and 120 (duodenal) minut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 80 publications
(139 reference statements)
0
4
0
Order By: Relevance
“…The content of lower than in other brown seaweed extracts, particularly when enzymatic ex used, with values in the range of 20 to 40% (w/w) [41]. In another work, it wa S. latissima showed the highest antioxidant activity, in comparison with Palm The ORAC values were studied, and it was found that the values of the antiox ity for P. palmata were lower, in comparison with the values achieved by S. l behavior could have been due to the origin of the seaweeds; P. palmata was controlled tanks, while S. latissima was cultivated in a marine farm (on subm lines) [42].…”
Section: Features Of Liquid Fractionsmentioning
confidence: 97%
See 1 more Smart Citation
“…The content of lower than in other brown seaweed extracts, particularly when enzymatic ex used, with values in the range of 20 to 40% (w/w) [41]. In another work, it wa S. latissima showed the highest antioxidant activity, in comparison with Palm The ORAC values were studied, and it was found that the values of the antiox ity for P. palmata were lower, in comparison with the values achieved by S. l behavior could have been due to the origin of the seaweeds; P. palmata was controlled tanks, while S. latissima was cultivated in a marine farm (on subm lines) [42].…”
Section: Features Of Liquid Fractionsmentioning
confidence: 97%
“…The ORAC values were studied, and it was found that the values of the antioxidant capacity for P. palmata were lower, in comparison with the values achieved by S. latissima. This behavior could have been due to the origin of the seaweeds; P. palmata was cultivated in controlled tanks, while S. latissima was cultivated in a marine farm (on submerged longlines) [42].…”
Section: Features Of Liquid Fractionsmentioning
confidence: 99%
“…The digestibility of seaweed proteins can vary depending on the species, seasonal variations, and the presence of other compounds (phenols, polysaccharides, dyes) (Vasconcelos et al., 2023). Heat treatment can effectively increase the bioavailability of protein obtained from the macroalgae species P. palmata without negatively impacting the content of essential amino acids (Maehre et al., 2016).…”
Section: Nutritional Value Bioaccessibility and Biofunctionality Of A...mentioning
confidence: 99%
“…A rat study showed low digestibility of protein from S. latissima; however, the rats were fed whole S. latissima, and the digestibility was presumed to improve by using protein-enriched S. latissima extracts, potentially in combination with other high-quality protein sources (Juul et al 2022). Information about the bioavailability of protein from S. latissima is scarce, but a study of protein release in an in vitro digestion model showed a protein release of 52.7% after 120 min of duodenal digestion (Vasconcelos et al 2023).…”
Section: Food and Feedmentioning
confidence: 99%